The Effect of Problem Based Learning Models on Practicum Based Argumentation Skills on Heat to Electricity Conversion Material - Irfan Pratama; Eko Suyanto; I Dewa Putu Nyeneng (JURNAL SPEKTRA, 2021)
This study aims to determine the effect of problem based learning models on student-based argumentation skills on heat to electricity conversion nature. The population of this research is all students of XII SMA Negeri 4 Bandarlampung. The selection of research samples using purposive sampling technique with a sample of class XII Science 3 totale sample are 30 students as an experimental class. The research design used was One Group Pretest-Posttest Design. Data were tested by N-gain analysis, normality test, and Paired Sample T-Test. Based on research conducted, using the Paired Sample T-Test, the Sig. (2-Tailed) is less than 0.05 which is 0,000, so it can be stated that there is an influence of problem based learning models on practicum-based student argumentation skills in the method of converting heat to electricity. The average N-gain (g) of argumentation skills in the experimental class is 0.80 with a high category. Based on the results of student argumentation tests show that 89.5% are categorized as Claims, namely students are able to express their opinions in written form based on the understanding of the questions given, 83.0% are categorized as Data, ie students understand the questions given so that they can write down any information based on the knowledge they know, 80.2% is categorized as a warrant, ie students are able to explain the relationship between Data and Claims. This shows that the problem based learning model is very effective and has a big impact on the improvement of argumentation skills. The problem based learning model can improve students' argumentation skills.